2022
DOI: 10.3389/fonc.2022.945915
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization plus lenvatinib with or without programmed death-1 inhibitors for patients with unresectable hepatocellular carcinoma: A propensity score matching study

Abstract: PurposeWe conducted a retrospective study to compare transarterial chemoembolization (TACE) plus lenvatinib plus programmed death-1 (PD-1) inhibitors with TACE plus lenvatinib in patients with unresectable hepatocellular carcinoma (HCC).Patients and methodsPatients with HCC were analyzed from January 2018 to January 2022 in three hospitals. Patients received TACE plus lenvatinib with or without PD-1 inhibitors (TACE+L+PD-1 or TACE+L, respectively). The baseline characteristics of the two groups were compared, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…No grade 4 AE occurred in these patients, which may be explained by the dosage reduction of lenvatinib once grade 3 AE occurs. These data are similar to those of the previous studies in primary HCC ( 11 , 18 ), and we concluded that the LEN-TAP regimen is safe and tolerable in urHCC patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No grade 4 AE occurred in these patients, which may be explained by the dosage reduction of lenvatinib once grade 3 AE occurs. These data are similar to those of the previous studies in primary HCC ( 11 , 18 ), and we concluded that the LEN-TAP regimen is safe and tolerable in urHCC patients.…”
Section: Discussionsupporting
confidence: 91%
“…According to our data, only one patient achieved conversion resection after 4 months of LEN-TAP treatment, which was significantly lower than the data in primary advanced-stage HCC according to previous reports ( 18 ). This may be partially because of the biological features of recurrent hepatocellular carcinoma and its special tumor microenvironment ( 16 ).…”
Section: Discussioncontrasting
confidence: 87%
“…The surgical and nonsurgical groups had median OS of 38.3 months and 23.2 months, respectively, and the median OS of the non-surgical patients was consistent with that described previously. 22 , 23 The 1, 2, 3, and 4-years OS rates of surgical and nonsurgical groups were 98.0%, 88.0%, 83.0%, 62%, and 78.0%, 51.0%, 41.0%, 41.0%, respectively ( P < .001). Therefore, for intermediate-advanced HCC patients who received local-plus-systemic therapy initially and successful down-staging to meet the criteria for surgical resection, surgical therapy could improve patient’s OS.…”
Section: Discussionmentioning
confidence: 94%
“…8,[12][13][14][15][16] Inspiringly, recent trials have proven striking efficacy of lenvatinib plus PD-1 inhibitors in patients with unresectable HCC. 8,15,16 Although there was insufficient evidence that the addition of PD-1 inhibitor to lenvatinib was superior to lenvatinib monotherapy, some retrospective studies, 6,[34][35][36][37][38] including ours, have shown that Len-TACE in combination with PD-1 inhibitor conferred improved response rate and survivals over Len-TACE for advanced HCC. In the present study, with the triple treatment of Len-Sin-TACE, remarkable clinical benefits in ORR, PFS and OS were achieved despite the extensive tumour burden on the patients.…”
Section: Discussionmentioning
confidence: 97%